2013
DOI: 10.1007/s00404-013-3132-1
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and functional biomarkers in ovarian response

Abstract: AMH and AFC were found to be the best ovarian reserve tests that can determine the total oocyte count retrieved, without any significant effects on pregnancy rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 25 publications
2
42
2
5
Order By: Relevance
“…However, unlike our re-sults, Vural et al found that age was significantly higher in the poor responder group [31]. The age-related decline in female fertility is most likely due to the decline in both the quantity and quality of oocytes.…”
Section: Items Area Under the Curve (Auc)contrasting
confidence: 97%
“…However, unlike our re-sults, Vural et al found that age was significantly higher in the poor responder group [31]. The age-related decline in female fertility is most likely due to the decline in both the quantity and quality of oocytes.…”
Section: Items Area Under the Curve (Auc)contrasting
confidence: 97%
“…Ganidou et al [28] demonstrated that the use of maternal age, AMH and FSH variables can very well and with high accuracy predict the excessive ovarian response. The study by Vural et al [29] also showed that maternal age is directly related with poor ovarian response and the odds of a poor response will be greater with the increase in maternal age. Assessment of ovarian reserve before utilizing assisted reproductive technology is a very important issue, and knowing that the ovarian response would be poor or excessive, allows the doctor to choose the final method of stimulation to reduce the side effects such as OHSS and to minimize cycle cancellation [30].…”
Section: Discussionmentioning
confidence: 91%
“…However, with considering a greater area under curve for no response compared to poor response and the lower number of false positives for no ovarian response, the probability of an individual with AMH level less than 1.2 being in the no response class was higher than being in poor response class. It should be noted that different categories have been presented for the ovarian reserve in various studies all of which are similar [29,31], also the estimated areas under the ROC curves in this study are better compared to the past and recent studies and indicates better accuracy of estimates in this study [26,32]. It should also be noted that in this study, the positive diagnostic likelihood ratios, which were related to former and latter likelihood of developing the disease, were numbers greater than 1 and along with the other reported add values in Table 3, encourage the physicians to use AMH levels for predicting ovarian response in women with infertility problems.…”
Section: Discussionmentioning
confidence: 97%
“…Research on infertility has evolved with constant studies and technological advances due to the increase of infertile couples who seek assisted reproduction (AR) services. [1,2] The recruitment and development of multiple ovarian follicles are key to treatment [3,4]The correct assessment of the ovarian reserve is a central issue in the management of patients with infertility. [1,3,5]The goal is to predict the chances of response to the induction and select the -optimal‖ dose for the ovarian hyperstimulation.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] The recruitment and development of multiple ovarian follicles are key to treatment [3,4]The correct assessment of the ovarian reserve is a central issue in the management of patients with infertility. [1,3,5]The goal is to predict the chances of response to the induction and select the -optimal‖ dose for the ovarian hyperstimulation. [3,6] .Female reproductive aging is a process that follows the generally accepted theory that over time, oocytes decrease in quantity and quality and do not regenerate [7].…”
Section: Introductionmentioning
confidence: 99%